THE RELATIONSHIP OF PARENTING SELF-EFFICACY AND COMMUNITY PEER GROUP SUPPORT WITH FEEDING PRACTICES AND NUTRITIONAL STATUS OF PRESCHOOL CHILDREN - Yuni Riska Hadi; Nadia Rahma Putri; Nita Indah Lestari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Nutritional issues among preschool children remain a concern, as they are influenced by feeding practices and parenting factors. This study aimed to analyze the relationship of parenting self-efficacy and community peer group support with the feeding practices and nutritional status of preschool children. A quantitative method with a cross-sectional design was employed. The study population consisted of mothers with preschool-aged children at TK PGRI 3 Gambiran, Genteng, Banyuwangi; a total sampling technique was used to select 40 respondents. Data were collected via questionnaires and analyzed using the Spearman test. The results revealed significant relationships between parenting self-efficacy and both feeding practices (p=0.000; r=0.552) and nutritional status (p=0.002; r=-0.469). Additionally, peer group support was associated with feeding practices (p=0.002; r=0.468) and nutritional status (p=0.003; r=-0.463). Respondents with high levels of self-efficacy and community support tended to exhibit optimal feeding practices and have children with normal nutritional status.